МЕТОДИЧЕСКИЕ ПОДХОДЫ К ОБУЧЕНИЮ ЭВФЕМИЗМАМ (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article focuses on the definition of the significance of euphemisms in language teaching and the methodological approaches used in their use. We know that learning a language requires learning not only the grammatical structure, lexicon, phonetics of that language, but also the culture of speech and expressions related to that language. Because of this, learning euphemisms related to the language serves to form the culture of speaking in order to make the speech fluent and meaningful, to be able to get out of uncomfortable situations freely.